The human firewall: Increasing digital awareness and literacy for consumer protection - Imani, Tita Amalia Nur; Prastyanti, Rina Arum (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In the evolving digital era, consumers are increasingly vulnerable to various cyber threats such as online fraud, identity theft, and misuse of personal data. This paper discusses the concept of